Silicon wafer material options for highly efficient p-type PERC solar cells - Dullweber, Thorsten; Kranz, Christopher; Baumann, Ulrike; Hesse, Rene; Walter, Dominic; Schmidt, Jan; Altermatt, Pietro; Brendel, Rolf (Conference record of the IEEE Photovoltaic Specialists Conference, 2013)
PERC solar cells targeted for industrial mass production mainly apply p-type boron-doped silicon wafers. However, boron-doped wafers are subject to light-induced degradation which can decrease the efficiency during solar cell operation. In this paper, we evaluate Cz and monolike silicon wafer materials with different resistivity and oxygen concentration and their application to high-efficiency PERC solar cells. Test wafer results show that both, lower oxygen concentrations as well as higher resistivity increase the carrier lifetime post LID from 105 μs up to 564 μs. PERC solar cells processed with these wafers achieve efficiencies between 19.9% and 20.2%. The light-induced degradation of the efficiency is reduced from 0.47% abs. for the standard 2 Ωcm Cz to around 0.3% abs. for 5 Ωcm Cz wafers and low oxygen MCz wafers. The lowest efficiency degradation of 0.17% abs. is obtained for the monolike wafers. The experimental results are in good accordance with 2-dimensional simulations using Sentaurus device taking into account the measured injection dependent minority carrier lifetimes.